Examination Malpractice as Determinant for Poor Academic Performance of Students in Agricultural science in Ife Central Local Government, Osun State - Festus Femi Oloidi (Ömer Gökhan Ulum, 2023)
This paper investigates examination malpractice as one of the determinants of poor performance in agricultural science among students in secondary schools in Ile - Ife. This will help in identifying the major factors responsible for this, and how to improve the students' performance in agricultural science so as to build students in developing more interest in the subject for better agricultural productivity at all levels. The descriptive research survey type was used. The population is made of all senior secondary school students offering agricultural science and agricultural science teachers of selected schools in Ife central local government. Two hundred secondary school students were selected. Fourty students were randomly selected from each of the five schools from the local government. Also, two agricultural science teachers were selected each from the five schools in the local government. Data were analyzed using frequency counts and percentages. Findings revealed that there were examination malpractices among students in Agricultural science. Poor performance of students in agricultural science as a result of examination malpractice reduces the interest of young secondary school leavers especially youths in the area of agriculture.